Worldview and resource development conflict: an analytical approach. (2017) - Lytle, Murray; Hitch, Michael
Resource developments can be complicated affairs in which groups with a multitude of differing worldviews dedicate themselves to putting a stop to what the earnest developer believes to be a net benefit to mankind. From the perspective of the resource developer, an understanding of the worldview of the people in the area to be explored and perhaps developed will be very useful in predicting the potential for future conflict. More importantly such knowledge will cause the resource developer to understand the history of his new neighbours and this is never a bad thing. This paper is based on the hypothesis that there is a relationship between an individual's underlying worldview and how supportive that individual is of resource development. The paper defines worldview and illustrates how societies and civilisations with dramatically different creative and economic energies result from different worldviews. To test the hypothesis, a questionnaire was created to build a database of responses for subsequent analysis to see if those responses are predictive of either sympathy with or antipathy to resource development. Using factor and multivariate regression analysis, the correlations between worldview responses and willingness to accept resource development were calculated for a variety of groups of respondents.